Effects of Branched Fins on Alumina and N-Octadecane Melting Performance Inside Energy Storage System - Weera, Wajaree; Maneengam, Apichit; Saeed, Abdulkafi Mohammed; Aissa, Abderrahmane; Guedri, Kamel; Younis, Obai; Marzouki, Riadh; Asogwa, Kanayo K. (Frontiers in Physics, 2022)
The importance of Phase change material (PCM) energy storage systems is no longer new in the industry. However, the influence of using branched fins inside the energy storage system on the melting process of alumina nanoparticles and n-octadecane has not been reported in the literature. Consequently, the outcome of a study on the numerical simulation for optimizing the melting performance of a PCM in various tubes, including those with branching fins is presented in this report. Four examples were assessed in relation to a suspension of alumina nanoparticles and n-octadecane paraffin that contains heated fins. A numerical technique based on the Galerkin finite element method (GFEM) was used to solve the dimensionless governing system. The average liquid percentage over the flow zone in question was computed. The primary results indicated that altering the number of heated fins might affect the flow structures, the system’s irreversibility, and the melting process. Case four, with eight heated fins, likewise produces the greatest average liquid fraction values and completes the melting process in 850s. Additionally, when 6% nano-enhanced PCM was used instead of pure PCM, the melting process is accelerated by 28.57 percent.